2019
DOI: 10.1007/s12178-019-09529-7
|View full text |Cite
|
Sign up to set email alerts
|

The Pivot Shift: Current Experimental Methodology and Clinical Utility for Anterior Cruciate Ligament Rupture and Associated Injury

Abstract: Purpose of Review The purpose of this manuscript is to (1) examine the history, techniques, and methodology behind quantitative pivot shift investigations to date and (2) review the current status of pivot shift research for its clinical utility for management of anterior cruciate ligament (ACL) rupture with associated injuries including the anterolateral complex (ALC). Recent Findings The pivot shift is a useful physical exam maneuver for diagnosis of rotatory instability related to ACL tear. Recent evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 70 publications
1
38
0
2
Order By: Relevance
“…The pivot-shift test is the most specific physical examination test for the diagnosis of anterior cruciate ligament (ACL) injuries. 2,23,33,34,40 The pivot shift is a cornerstone of knee laxity assessment because it is an important preoperative predictor of clinical outcomes, serves to guide an appropriated index of suspicion for injury to the secondary restraints, and is the primary outcome measure that quantifies improvement in knee stability after ACL reconstruction. The presence of a high-grade preoperative pivot shift is associated with an increased risk of rerupture after ACL reconstruction and an increased risk of persistent rotatory instability after surgery as compared with a low-grade pivot shift.…”
mentioning
confidence: 99%
“…The pivot-shift test is the most specific physical examination test for the diagnosis of anterior cruciate ligament (ACL) injuries. 2,23,33,34,40 The pivot shift is a cornerstone of knee laxity assessment because it is an important preoperative predictor of clinical outcomes, serves to guide an appropriated index of suspicion for injury to the secondary restraints, and is the primary outcome measure that quantifies improvement in knee stability after ACL reconstruction. The presence of a high-grade preoperative pivot shift is associated with an increased risk of rerupture after ACL reconstruction and an increased risk of persistent rotatory instability after surgery as compared with a low-grade pivot shift.…”
mentioning
confidence: 99%
“…After identi cation of the structure, a histological and radiological MRI study was initiated (AOL visualized in x examined specimens). The authors studied the anatomy and biomechanics of the region 5,8,9,10,16,17,18,19,21,22 and developed a reasoning termed the Theory of Tibial Quadrants, which facilitates the understanding of circumferential joint structures and rotational control (Figure 4). The tibial surface is divided into an anterior and posterior portion through a band that connects the femoral transepicondylar plane, the origin or near origin of the important ligaments that travel toward the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, following ACL injury, the iliotibial band is the primary restraint to tibial internal rotation during a simulated pivot shift [24]. Similar biomechanical studies have found that the ALC experiences the highest in situ forces and resists rotatory knee instability at 90°of flexion and insignificant in situ force at 30°of flexion where rotatory knee instability is normally assessed [4,60].…”
Section: Biomechanics Of the Alc And Residual Rotatory Knee Instabilitymentioning
confidence: 91%